8n-2=6n-15

Simple and best practice solution for 8n-2=6n-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8n-2=6n-15 equation:


Simplifying
8n + -2 = 6n + -15

Reorder the terms:
-2 + 8n = 6n + -15

Reorder the terms:
-2 + 8n = -15 + 6n

Solving
-2 + 8n = -15 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
-2 + 8n + -6n = -15 + 6n + -6n

Combine like terms: 8n + -6n = 2n
-2 + 2n = -15 + 6n + -6n

Combine like terms: 6n + -6n = 0
-2 + 2n = -15 + 0
-2 + 2n = -15

Add '2' to each side of the equation.
-2 + 2 + 2n = -15 + 2

Combine like terms: -2 + 2 = 0
0 + 2n = -15 + 2
2n = -15 + 2

Combine like terms: -15 + 2 = -13
2n = -13

Divide each side by '2'.
n = -6.5

Simplifying
n = -6.5

See similar equations:

| 9rs-3=t | | 8x+12y=156 | | .7+1x=-.6 | | 36+7= | | 5n+2-7= | | 8(4x-2.5)=16 | | 4+-0.5y=x | | 3(1-x)=-(7x+5) | | 4(z+2)-7z=6(-0.5z+1)+2 | | 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 |

Equations solver categories